2000
DOI: 10.1111/j.1749-6632.2000.tb05309.x
|View full text |Cite
|
Sign up to set email alerts
|

The Eradication of Contagious Bovine Pleuropneumonia from South Western Africa: A Plan for Action

Abstract: Contagious bovine pleuropneumonia (CBPP) caused by the Mycoplasma mycoides subspecies mycoides SC is one of the major plagues affecting cattle. With the imminent eradication of rinderpest from Africa, CBPP will become the major epidemic disease on the continent, because the majority of countries in sub‐Saharan Africa have the infection in their cattle. There is an enclave of CBPP on the borders of Angola, Botswana, Namibia, and Zambia. There has been endemic infection in the cattle herds on the borders of Ango… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 3 publications
(4 reference statements)
1
30
0
Order By: Relevance
“…The high sero-geospatial burden distribution patterns obtained in the two production systems, which are invariably extensive in nature, are in agreement with the previous reports that the extensive nature of the husbandry systems exposed stocks to different geographical factors, which exacerbate CBPP occurrence (Nawathe 1992;Nwanta and Umoh 1992;Jiuqing et al 2011). The higher CBPP sero-geospatial burden in the nomadic system than in the sedentary system is in consonance with previous findings that burden of CBPP varies according to the cattle management system and tends to be higher in more extensive cattle husbandry systems (Windsor 2000).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The high sero-geospatial burden distribution patterns obtained in the two production systems, which are invariably extensive in nature, are in agreement with the previous reports that the extensive nature of the husbandry systems exposed stocks to different geographical factors, which exacerbate CBPP occurrence (Nawathe 1992;Nwanta and Umoh 1992;Jiuqing et al 2011). The higher CBPP sero-geospatial burden in the nomadic system than in the sedentary system is in consonance with previous findings that burden of CBPP varies according to the cattle management system and tends to be higher in more extensive cattle husbandry systems (Windsor 2000).…”
Section: Discussionsupporting
confidence: 78%
“…CBPP is regarded as the most serious infectious disease affecting cattle in sub-Saharan Africa (Amanfu 2009;Marobela-Raborokgwe 2011) and impacts animal health and poverty of livestock-dependent people, especially the livestock pastoralists, through decreased animal productivity, reduced food supply for households, and the cost of control measures (Windsor 2000;Tambi et al 2006;Jiuqing et al 2011). The disease constitutes a barrier to trade in many African countries due to reduction in the value of livestock and the income of many value chain stakeholders (Nicholas et al 2008;Jores et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Contagious bovine pleuropneumonia is believed to have been present in East and West Africa prior to the colonial era. The introduction of CBPP into southern Africa from Europe in 1854 and its subsequent spread as far north as Angola are well documented (Windsor, 2000). These regional differences are borne out by recent molecular epidemiologic studies that have demonstrated three African lineages of CBPP (Lorenzon et al, 2003).…”
Section: Introductionmentioning
confidence: 91%
“…Contagious bovine pleuropneumonia surveillance and control programmes were dramatically curtailed (Windsor, 2000). Public empowerment and the recognition of the pervasive negative effects of movement control on pastoral livelihoods decreased the acceptability of this tool as a control option.…”
Section: Introductionmentioning
confidence: 99%
“…mycoides small colony type (SC). It represents a major threat to raising cattle, particularly in Africa, where it creates great economic losses in regions of endemicity (6,15,21). CBPP was eradicated in the middle of the 20th century in the industrialized continents (5), but it reemerged in a few European countries in 1980 to 1999 in a milder, more insidious form that appeared to be largely chronic and showed a low mortality rate (11).…”
mentioning
confidence: 99%